Occurence of arcobacter species in farm chicken and chicken meat at reail outlets in Malaysia - Lemma, Amare Berhanu (2009)
The genus Arcobacter comprises the former “aerotolerant campylobacters” that are recognized recently as emerging, potential food- and water-borne pathogens. Like their closely related campylobacters, arcobacters are major contaminants of poultry products rendering poultry in general and chicken in particular significant risk factors to humans. A number of protocols have so far been described to detect Arcobacter on food although their apparent deficiencies and the likely underestimation therein of the actual rate of contamination are well emphasized. Furthermore, there is a general scarcity of data on the occurrence of the bacteria in the food chain in Malaysia. The present study was, therefore, undertaken to evaluate the performances of existing Arcobacter isolation protocols for maximum detection of naturally contaminated chicken meat, to determine the occurrence of Arcobacter at two levels (chicken meat at retail outlets and chickens in the farms) and to identify the species of the isolates.Forty-eight retail chicken meat samples were subjected to three established protocols [modified Lammerding (method I), Steele and Mc Dermott (method II), Houf (method III)], and an ‘in-house’ method (method IV) comprising the enrichment procedure of Houf and the plating media and techniques specified in the modified Lammerding protocol. Method II failed to recover the organisms from any of the samples but Arcobacter were detected by the other protocols (methods I, III, and IV). The Arcobacter isolates were identified by a multiplex PCR as Arcobacter butzleri from 30 (62.5%) chicken meat samples. By comparison, the ‘in-house’ protocol (method IV) recovered the bacteria from a greater number of samples (24 of 48) than the modified protocol of Lammerding (12 of 48) (p= 0.019), or the protocol of Houf (17 of 48) (p= 0.046). Each of the methods involved some degree of false negative results with the high frequency of positive samples detected by the ‘in-house’ protocol (50%). This suggested that the ‘in house’ method offer a more accurate estimate of the actual occurrence of Arcobacter on food than either of the parent protocols (method I: 25%; method III: 35.42%) thereby making it a good alternative to consider whenever available resources proscribe the simultaneous use of multiple methods. It is recommended that further verification and/or validation of the ‘inhouse’ protocol be made prior to its adoption. To determine the frequency of occurrence of Arcobacter and the species distribution, fresh/‘warm’ (n= 61) and chilled (n= 62) chicken meat parts were purchased from various retail outlets in Selangor. Forty eight of the 123 (prevalence: 39.02%; range: 0 – 88.2%) chicken meat parts selected from five sampling sites (retail outlets) were found to be Arcobacter-positive with A. butzleri as the only species isolated. The fresh/’warm’ chicken meat portions had a higher contamination frequency (41%) than the chilled chicken meat parts (37.1%) although the difference was not statistically significant (2= 0.2; p= 0.655). A farm-level survey was also conducted to assess the presence of Arcobacter species in live chicken so as to determine whether intestinal carriage of the bacteria accounted for its high rate of occurrence on the chicken meat portions. The bacteria were not detected in any of 210 cloacal swabs collected from six chicken farms in Southern (Melaka and Johor ) and Central (Selangor) regions of peninsular Malaysia probably supporting the views that poultry are less likely hosts for Arcobacter. Environmental factors such as water may play the role for the presence of Arcobacter on chicken meat. This is the first large scale study on the occurrence of Arcobacter species in the Malaysian food production chain and the first to establish the distribution of species. Overall, the findings of the study indicated arcobacters to constitute a major proportion of the chicken meat microbiota rendering this product a significant risk factor for human acquisition of the organisms.